THE PHENOMENON OF LEARNING USING ZOOM MEETING AT SMK PGRI 37 JAKARTA - Sara Sahrezad; Maria Cleopatra; Lusiana Wulansari; Arief Muda Kusuma; Lengsi Manurung; Adhis Darussalam Pamungkas; Sabrina Alfradita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
This study aims to determine the phenomenon of learning using Zoom Meetings that occur in class XII marketing subjects Marketing SMK PGRI 37 Jakarta. This research is a qualitative research with the type of phenomenology. The sampling technique used was purposive sampling with the research subject being a marketing subject teacher for class XII Marketing and 3 students in class XII Marketing. Data collection techniques are carried out through observation, interviews, and documentation. The results of this study indicate that the Zoom Meeting application as a video conference application is very adequate to be used in online learning media. If it is seen from the results of learning the average value of marketing subjects for class XII Marketing students in online learning for the even semester 2020/2021 has increased compared to the learning outcomes for class XII Marketing students for odd semesters, it can be said that online learning using the Zoom Meeting application is effective. Evaluation is not carried out in full, in the sense that the teacher cannot see the students directly. The results of the learning evaluation are classified as good average.